An incidental concurrence causing gastric outlet obstruction - R., Abhirup H.; Kenchetty, Priyanka; Chidananda, Aishwarya K. (International Surgery Journal, 2021)
Phytobezoar which is described as an undigested or incompletely digested food. It is an odd cause of gastric outlet obstruction (GOO). The aim of this study is to present and discuss a case of GOO caused by cicatrised duodenal ulcer with a phytobezoar. 71-year-old male, presented with abdominal pain and vomiting (non-bilious) since 3days with peptic ulcer disease for 4 years. Examination and investigations revealed a bezoar requiring emergency surgical intervention. An exploratory laparotomy was conducted. A bezoar was palpated in the stomach and removed through posterior gastrotomy. Vagotomy with Posterior Gastrojejunostomy was done as drainage procedure for cicatrised Duodenal ulcer. GOO caused by phytobezoar can co-exist in patients with previous history of peptic ulcer disease and cicatrised duodenal ulcer. Urgent laparotomy may be indicated.